Teachers’ Efforts in Increasing Eighth Grade of Modern Islamic Boarding School Students’ Learning Motivation in Arabic Class - Eri Rahmawati; Dewi Fitriani; Ifa Lesintha Mukti; Wahyu Nurrohman (Universitas Pahlawan Tuanku Tambusai, 2022)
This article aims to analyze the teacher's efforts in increasing students' motivation to learn Arabic. The background of the research is at the Al-Kinana Modern Islamic Boarding School, Jambi City, to be precise in class VIII students. The focus of this research is not only discussing the teacher's efforts in increasing students' learning motivation, but also analyzing the various obstacles or obstacles experienced by students during the Arabic learning process. This study uses a qualitative approach with descriptive analytical study method. The research data collection instrument used interview and observation techniques. Then the data were analyzed through data reduction techniques, data presentation, and data verification. The results of this study conclude that the efforts of Arabic language teachers in increasing students' learning motivation in Arabic subjects for class VIII Pondok Pesantren Modern Al-Kinanah Jambi City are quite good, this can be seen from the various efforts made by teachers, such as: using the Lecture Method, Questions and Answers and Discussion while teaching Arabic learning. Then, give assignments to students individually, give praise (appreciation) to students who answer questions correctly, and give marks to each Arabic learning exercise. The obstacle faced by the teacher is the unpreparedness of the students in receiving the subject matter, and there are some students who pay less attention to the learning material when the teacher explains the material, and some are sleeping while the learning is taking place. Efforts made by teachers in overcoming these problems are by activating the classroom atmosphere by giving assignments and direct questions about Arabic learning materials.